(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Effective risk management techniques can be developed using big data analytics to find new dangers in data trends. Businesses may make quicker and better decisions with the help of the insights business users derive from pertinent data. Businesses can gain timely insights on sales, marketing, finances, product development, and other topics with the aid of data analytics. It enables teams within organisations to work together and get better results. Businesses can improve future business operations by analysing historical business performance. The researchers have collected the data from 200 employees working in information technology sector using survey method with the help of well-structured questionnaire. The researcher identified that descriptive research design and Non probability convenience sampling method is suitable for the research study. The findings of this study will be useful to many companies to sustain in the competitive world.